2021
DOI: 10.1016/j.jhazmat.2020.123391
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological safety and antibiotic resistance risks at a sustainable farm under large-scale open-air composting and composting toilet systems

Abstract: This study evaluated the microbial safety and antibiotic resistance risks of a sustainable ecological farm under large-scale open-air composting (OC) and green composting toilet systems (CT). Samples of livestock manure, compost, soil, vegetables, and rainwater were analysed to determine the best treatment of wastes and risk assessment of land application. Results showed that pathogenic bacteria (PB) in livestock manure was significantly greater than that in the surrounding topsoil, while the distribution of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Where feasible, the installation of barn flooring that could be subject to frequent runoff should be considered, along with the implementation of proper drainage systems. Finally, it is important to improve the monitoring of microbiologically safe biofertilizers through suitable indicators and to promote the use of safer composting methods, as previously discussed by other authors [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Where feasible, the installation of barn flooring that could be subject to frequent runoff should be considered, along with the implementation of proper drainage systems. Finally, it is important to improve the monitoring of microbiologically safe biofertilizers through suitable indicators and to promote the use of safer composting methods, as previously discussed by other authors [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, amoxicillin was the least effective antibiotic since 11 of the 19 strains showed resistance to this compound. Liu et al (2021) also reported the presence of microorganisms isolated of manures resistant to this antibiotic. The extensive use of amoxicillin in both humans and animals has increased resistance to this compound (Sodhi et al, 2021).…”
Section: Antibiotic Resistancementioning
confidence: 94%
“…According to the maximum value of the bacterial Minimum Inhibition Concentration, AMX-resistant bacteria and TCB were counted on R2A medium with and without 32 mg/L AMX by referring to previous experience ( Liu et al, 2020 ). The colony formation unit (CFU) per gram was calculated by the formula (1) .…”
Section: Methodsmentioning
confidence: 99%